Melatonin treatment improves ventricular conduction via upregulation of Nav1.5 channel proteins and sodium current in the normal rat heart - Durkina, Aleksandra V; Bernikova, Olesya G; Gonotkov, Mikhail A; Mikhaleva, Natalia J; Sedova, Ksenia A; Malykhina, Inna A; Kuzmin, Vladislav S; Velegzhaninov, Ilya O; Azarov, Jan E (Journal of pineal research, 2022)
Melatonin treatment was reported to reduce the risk of cardiac arrhythmias, and crucial for this antiarrhythmic action was the effect of melatonin on activation spread. The aim of the present study was evaluation of the mechanisms of this activation enhancement. Experiments were performed in a total of 123 control and melatonin-treated (10 mg/kg, daily, for 7 days) male Wistar rats. In epicardial mapping studies (64 leads, interlead distance 0.5 mm) in the anesthetized animals, activation times (ATs) were determined in each lead as dV/dt minimum during QRS complex under sinus rhythm. Epicardial pacing was performed to measure conduction velocity (CV) across the mapped area. Average left ventricular ATs were shorter in the treated animals as compared to the controls, whereas the minimal epicardial ATs indicating the duration of activation propagation via the ventricular conduction system did not differ between the groups. CV was higher in the treated groups indicating that melatonin affected conduction via contractile myocardium The area of Cx43-derived fluorescence, as well as the expression of Cx43 protein, was similar in ventricles in the control and melatonin-treated groups. Expression of Gja1 gene transcripts encoding Cx43, was increased in the last group. An uncoupling agent octanol modified myocardial conduction properties (time of activation, action potential upstroke velocity, passive electrotonic phase duration) similarly in both groups. On the other hand, the expression of both Scn5a gene transcripts encoding Nav1.5 proteins, as well as peak density of transmembrane sodium current were increased in the ventricular myocytes from the melatonin-treated animals. Thus, a week-long melatonin treatment caused the increase of conduction velocity via enhancement of sodium channel proteins expression and increase of sodium current in the ventricular myocytes.
Keywords: connexins; Rats; Up-Regulation; NAV1.5 Voltage-Gated Sodium Channel; upregulace; konexin 43; Connexin 43; mužské pohlaví; Rats, Wistar; sodium current; krysa rodu Rattus; sodium channels; conduction velocity; převodní systém srdeční; zvířata; Melatonin; Heart Conduction System; melatonin; Heart; sodík; potkani Wistar; Sodium; napěťově řízený sodíkový kanál, typ 5; srdce; Male; Animals